Restorative Justice in Customary Law: Alternative Dispute Resolution in Indigenous Communities - Suhermi (Journal of Adat Recht, 2024)
Restorative justice is an alternative approach to dispute resolution that emphasizes the restoration of relationships between the parties involved, in contrast to the retributive approach that focuses on punishment. Based on the concept of the rule of law, legal certainty in Indonesia can not only be achieved through the norms contained in the law, but also by considering the values that live in society, such as customary law. This research aims to explore the application of restorative justice in customary law as an out-of-court dispute resolution mechanism. This research uses a normative research method that focuses on the study of legal documents, especially those related to the implementation of alternative dispute resolution that has been promulgated as Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. The results show that customary law that emphasizes restorative justice is recognized and integrated in Law Number 30 of 1999, enabling out-of-court dispute resolution in a way that is more in line with local values. The recognition and integration of customary law in the national legal framework strengthens the role of customary law in achieving legal certainty in Indonesia, especially in the context of dispute resolution at the community level.